A Simple Three-term Conjugate Gradient Algorithm for Solving Symmetric Systems of Nonlinear Equations - M. Y. Waziri; L. Muhammad; J. Sabi’u (Institute of Advanced Engineering and Science, 2016)
This paper presents a simple three-terms Conjugate Gradient algorithm for solving Large-Scale systems of nonlinear equations without computing Jacobian and gradient via the special structure of the underlying function. This three term CG of the proposed method has an advantage of solving relatively large-scale problems, with lower storage requirement compared to some existing methods. By incoporating the Powel restart approach in to the algorithm, we prove the global convergence of the proposed method with a derivative free line search under suitable assumtions. The numerical results are presented which show that the proposed method is promising.